2016
DOI: 10.1002/jmv.24611
|View full text |Cite
|
Sign up to set email alerts
|

Different HIV‐1 env frames: gp120 and ASP (antisense protein) biosynthesis, and theirs co‐variation tropic amino acid signatures in X4‐ and R5‐viruses

Abstract: Antisense protein (ASP) is the new actor of viral life of Human Immunodeficiency Virus type 1 (HIV-1) although proposed above 20 years ago. The asp ORF is into complementary strand of the gp120/gp41 junction of env gene. The ASP biological role remains little known. Knowing the Env markers of viral tropism, a dataset of sequences (660 strains) was used to analyze the hypothetical ASP involvement in CCR5 (R5) and/or CXCR4 (X4) co-receptor interaction. Preliminarily, prevalence of ASP and gp120 mutations was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Altogether, this study strongly suggests that the asp gene which appeared concomitantly with, and is uniquely conserved within, the HIV-1 pandemic group M, is the 10th HIV-1 gene and that its transcriptional and/or translational products may endow the virus with an evolutionary advantage (Cassan et al, 2016). Of note, 1 year after this study, using an extensive sequence analysis (660 viral strains), another study found that asp mutations were associated with mutations of the hypervariable region V3 of env and thereby proposed that asp mutations could be linked to viral tropism and different co-receptor usage (Dimonte, 2017).…”
Section: Origin Evolution and Conservation Of The Asp Genementioning
confidence: 85%
“…Altogether, this study strongly suggests that the asp gene which appeared concomitantly with, and is uniquely conserved within, the HIV-1 pandemic group M, is the 10th HIV-1 gene and that its transcriptional and/or translational products may endow the virus with an evolutionary advantage (Cassan et al, 2016). Of note, 1 year after this study, using an extensive sequence analysis (660 viral strains), another study found that asp mutations were associated with mutations of the hypervariable region V3 of env and thereby proposed that asp mutations could be linked to viral tropism and different co-receptor usage (Dimonte, 2017).…”
Section: Origin Evolution and Conservation Of The Asp Genementioning
confidence: 85%
“…Two subsequent reports analyzed co-evolution of the ASP and ENV open reading frames. Dimonte studied the correlation between mutations in ASP and ENV, and CCR5 vs. CXCR4 coreceptor usage [ 78 ]. The author first used the G2P algorithm to predict the tropism of ~24,000 HIV-1 subtype B env sequences deposited in the Los Alamos HIV Sequence Database, and then analyzed the association of mutations in ASP with predicted coreceptor usage.…”
Section: Origin Conservation and Evolution Of Aspmentioning
confidence: 99%
“…The gp120 V3 loop becomes exposed upon binding of gp120 with CD4, contacts the coreceptor (CCR5 or CXCR4), and mediated virus entry into the target cell [ 79 ]. The author found eight sites on ASP where specific mutations are associated in a statistically significant manner with mutations in the V3 loop of gp120 and with CCR5/CXCR4 tropism; six of these eight mutations map in the extracellular/viral loop of ASP [ 78 ]. It should be underscored that the ASP ORF overlaps the env gene in the region of the V4 and V5 loops, but not V3.…”
Section: Origin Conservation and Evolution Of Aspmentioning
confidence: 99%
“…First, in a monumental study of approximately 23,000 HIV and SIV sequences, Cassan and colleagues convincingly showed that the ASP ORF is exclusively found in group M viruses and correlates with subtypes, or clades, responsible for the human pandemic [65]. Next, mutations in asp, not reflected in overlapping env sequences, are associated with CCR5 and CXCR4 tropism [66]. Finally, the effect of natural selection on asp as a functional gene was examined.…”
Section: Formulation Of the Hypothesis For An Hiv-1 Antisense Proteinmentioning
confidence: 99%